A descriptive study of demographics, triage allocations and patient outcomes for a private emergency centre in Pretoria for 2018 - Hedding, Kirsty (Division of Emergency Medicine, 2021)
Background Triage aims to detect critically ill patients and to prioritise those with time-sensitive needs. It also contributes to the overall efficiency of an emergency centre (EC). International systems have been relatively well researched; however, no data exists on the use of the SATS score in private healthcare settings in SA. Objectives This study aimed to describe the demographics, triage allocations, time spent in EC and disposition of all patients presenting to a private hospital EC in Pretoria, South Africa in 2018. Methods A retrospective descriptive study was undertaken. Data relating to demographics, triage, and hospital disposition were collected on all patients presenting to the EC during the 2018 calendar year. Descriptive data analyses were conducted in Microsoft Excel. Results A total of 29 055 patients were included in this study. More than half (57.6%) were adults aged 18 to 60 years and approximately one-fourth (27.5%) were paediatrics (<18 years). The majority of patients were triaged yellow (73.5%); 17.4% were triaged as red and orange. It took, on average, 28 minutes to be seen by a provider and patients spent an average of 2 hours and 20 minutes in the EC. Delays to be seen exceeded standards for red and orange patients at 8 and 18 minutes respectively, and the mean time these patients spent in the EC was higher (2h 51 minutes and 2h 47 minutes respectively). Most patients (76.1%) were discharged; 5.6% were admitted to ICU/high care, 14.4% to the general ward, and 3.9% either absconded or refused hospital treatment. Of patients triaged red and orange, 11.1% and 49.3% were discharged respectively, and these patients used the most resources . Conclusion This study found that most of the patients were triaged into low acuity categories (yellow and green) and discharged home. High acuity patients were usually admitted to ICU or high care; however, these patients experienced delays in being treated and admitted. Causes of these issues, and implications on patient outcomes remain unknown. Large numbers of high acuity patients were ultimately discharged home. Further studies are needed to understand the influence of triage accuracy on these patients' outcomes.